The global governance of HIV/AIDS : intellectual property and access to essential medicines - Aginam, Obijiofor, 1969-; Harrington, John, 1969-; Yu, Peter K. (Cheltenham, UK : Edward Elgar, 2013)
This important book brings together leading scholars from multiple disciplines, including intellectual property, human rights, public health, and development studies, as well as activists to critically reflect on the global health governance regime. The Global Governance of HIV/AIDS explores the implications of high international intellectual property standards for access to essential medicines in developing countries. With a focus on HIV/AIDS governance, the volume provides a timely analysis of the international legal and political landscape, the relationship between human rights and intellectual property, and emerging issues in global health policy. It concludes with concrete strategies on how to improve access to HIV/AIDS medicines. This interdisciplinary, global, and up-to-date book will strongly appeal to academics in law, international relations, health policy and public policy, as well as students, policymakers and activists.
Introduction / Obijiofor Aginam and John Harrington -- Communitarian globalism and disease : a normative orientation for global health governance / Obijiofor Aginam -- Is AIDS treatment sustainable? / Kenneth C. Shadlen -- Access to paediatric medicines : the global political economy of drug protection and supply for children in the developing world / Avram Denburg and Kelley Lee -- Trade agreements, intellectual property and access to essential medicines : what future role for the right to health? / James Harrison -- Re-visiting the patents and access to essential medicines dichotomy : an evaluation of TRIPs implementation and public health safeguards in developing countries / Tahir Amin -- Seizure of generic pharmaceuticals in transit based on allegations of patent infringement : a threat to international trade, development and public welfare / Frederick M. Abbott -- Patent licensing strategies for the research and development of pharmaceuticals in developing countries / Gail E. Evans -- Increasing access through incentives for innovation : the Health Impact Fund / Laura Biron -- Building IPC4D to promote access to essential medicines / Peter K. Yu -- The global governance of HIV/AIDS and the rugged road ahead : an epilogue / Peter K. Yu.
Includes bibliographical references and index.
Keywords: Drug accessibility; Drugs -- Patents; Intellectual property; HIV infections -- Treatment; AIDS (Disease) -- Treatment